2022
DOI: 10.1080/22221751.2022.2093133
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of viral replication, apoptosis and antiviral response by induction and mutual regulation of EGR and AP-1 family genes during coronavirus infection

Abstract: Coronaviruses have evolved a variety of strategies to exploit normal cellular processes and signalling pathways for their efficient reproduction in a generally hostile cellular environment. One immediate-early response gene (IEG) family, the AP-1 gene family, was previously shown to be activated by coronavirus infection. In this study, we report that another IEG family, the EGR family, is also activated in cells infected with four different coronaviruses in three genera, i.e. gammacoronavirus infectious bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Among them, GADD34 and GADD153 were significantly upregulated by IBV infection-induced ER stress response and play important roles in regulating IBV replication and virus-host interaction ( Liao et al, 2013 ; Wang et al, 2009a , Wang et al, 2009b ). Our studies also reveal the essential roles of EGR family genes, especially EGR1, in regulating coronavirus replication and pathogenesis, and SGK1 in virion assembly and release ( Yuan et al, 2022 ; Zhu et al, in preparation).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Among them, GADD34 and GADD153 were significantly upregulated by IBV infection-induced ER stress response and play important roles in regulating IBV replication and virus-host interaction ( Liao et al, 2013 ; Wang et al, 2009a , Wang et al, 2009b ). Our studies also reveal the essential roles of EGR family genes, especially EGR1, in regulating coronavirus replication and pathogenesis, and SGK1 in virion assembly and release ( Yuan et al, 2022 ; Zhu et al, in preparation).…”
Section: Discussionmentioning
confidence: 59%
“…The top 10 genes with the most significant differential expression during IBV infection were FOXJ1, FOSB, cFOS, EGR4, CRB2, CASS4, ZNF474, RRAD, EGR3 and EGR1. Using this information as starting points, the regulatory roles of several DEGs and related cellular pathways in coronavirus replication and pathogenesis were studied in detail in our previous publications ( Li et al, 2022 ; Yuan et al, 2020 , 2022 ; Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EGR1 was found to be activated via ERK1/2 signaling and loss of EGR1 via siRNA resulted in a significant decrease in viral replication (~2 log 10 ) suggesting EGR1 may play a role in viral replication (Cai et al, 2006). More recent studies found EGR1 mRNA and protein levels are upregulated following infection with infectious bronchitis virus (IBV) in H1299, Vero, and DF1 cells (Yuan et al, 2022). Other coronaviruses examined, including porcine epidemic diarrhea virus (PEDV), human coronavirus (HCoV)-229E, and HCoV-OC43, were also found to activate EGR1 at both the mRNA and protein level following infection in both H1299 and Vero cells (Yuan et al, 2022).…”
Section: Coronaviridaementioning
confidence: 99%
“…More recent studies found EGR1 mRNA and protein levels are upregulated following infection with infectious bronchitis virus (IBV) in H1299, Vero, and DF1 cells (Yuan et al, 2022). Other coronaviruses examined, including porcine epidemic diarrhea virus (PEDV), human coronavirus (HCoV)-229E, and HCoV-OC43, were also found to activate EGR1 at both the mRNA and protein level following infection in both H1299 and Vero cells (Yuan et al, 2022). Following siRNA-mediated knock-down of EGR1, it was shown that loss of EGR1 has no significant impact on IBV replication but knock-down cells had significantly higher percentages of PARP cleavage, an indicator of cell death, which suggests that EGR1 may function as a survival factor during IBV infection of H1299 cells (Yuan et al, 2022).…”
Section: Coronaviridaementioning
confidence: 99%
See 1 more Smart Citation